2014
DOI: 10.1111/1758-2229.12204
|View full text |Cite
|
Sign up to set email alerts
|

A trans‐outer membrane porin‐cytochrome protein complex for extracellular electron transfer by Geobacter sulfurreducensPCA

Abstract: The multi-heme, outer membrane c-type cytochrome (c-Cyt) OmcB of Geobacter sulfurreducens was previously proposed to mediate electron transfer across the outer membrane. However, the underlying mechanism has remained uncharacterized. In G. sulfurreducens, the omcB gene is part of two tandem four-gene clusters, each is predicted to encode a transcriptional factor (OrfR/OrfS), a porin-like outer membrane protein (OmbB/OmbC), a periplasmic c-type cytochrome (OmaB/OmaC) and an outer membrane c-Cyt (OmcB/OmcC) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
146
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(159 citation statements)
references
References 50 publications
12
146
1
Order By: Relevance
“…Microbial metabolism of electrons that are not associated with a chemical element, that is, 'free' electrons, is an intriguing metabolic capacity that has been primarily investigated in insoluble metalreducing microorganisms, such as Shewanella or Geobacter species (Bond and Lovley, 2003;Hartshorne et al, 2009;Coursolle et al, 2010;Clarke et al, 2011;Lovley, 2012;Liu et al, 2014;Malvankar and Lovley, 2014;Pirbadian et al, 2014;TerAvest et al, 2014). In addition to these anodic microbial processes, recent studies have revealed that some microorganisms can take up 'free' cathodic electrons from conductive minerals during interspecies electron transfer (Kato et al, 2012) or from abiotically reduced surfaces such as deep sea hydrothermal vent chimneys (Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metabolism of electrons that are not associated with a chemical element, that is, 'free' electrons, is an intriguing metabolic capacity that has been primarily investigated in insoluble metalreducing microorganisms, such as Shewanella or Geobacter species (Bond and Lovley, 2003;Hartshorne et al, 2009;Coursolle et al, 2010;Clarke et al, 2011;Lovley, 2012;Liu et al, 2014;Malvankar and Lovley, 2014;Pirbadian et al, 2014;TerAvest et al, 2014). In addition to these anodic microbial processes, recent studies have revealed that some microorganisms can take up 'free' cathodic electrons from conductive minerals during interspecies electron transfer (Kato et al, 2012) or from abiotically reduced surfaces such as deep sea hydrothermal vent chimneys (Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of a porincytochrome (Pcc) protein complex has recently been discovered. Composed of three proteins; a porin like outer membrane protein, a periplasmic cytochrome and an outer membrane cytochrome, the Pcc complex is thought to be responsible for facilitating electron transfer to the outside of the cell [33] . Furthermore, the outer membrane cytochrome OmcZ, has been found to be localised at the biofilm-electrode interface of current producing cells of G. sulfurreducens [34] and is proposed to act as an electrochemical gate, permitting the transfer of electrons from the electroactive biofilm to the electrode [34].…”
Section: Figure 22: Cytochromes Involved In the Extracellular Electrmentioning
confidence: 99%
“…A speculative model of the Geobacter EET based on previous research and suggestions [23,31,33,161,162,171,181] is shown in Figure 5.9. This model suggests that electrons are transferred from the menoquinone pool within the inner membrane to MacA which then transfers electrons PpcA [163], which shuttles the electrons across the periplasm to a Pcc complex [33].…”
Section: Abundance Of Eet Related Proteinsmentioning
confidence: 99%
See 2 more Smart Citations